Упростите числовое выражение: (√21+ √3)^2 - 6√7 (числитель) весь деленный на 12,тоесть:

(√21+ √3)^2 - 6√7

__________________

12

2

Ответы и объяснения

2013-03-31T23:56:37+04:00

(√21+ √3)^2 - 6√7

__________________ = (21+ 67+3-67)= 24/12=2

               12                            12

Ответ:2

2013-03-31T23:57:01+04:00

 (√21+ √3)^2 - 6√7         21+2√21*√3+3-6√7     24+2*√9*√7-6√7       24+6√7 -6√7  

__________________=------------------------------ = --------------------------- =--------------------- = 2

               12                            12                          12                           12